Medieval sovereignty - Latham, Andrew (Past imperfect (ARC Humanities Press), 2022)
Through a focused and systematic examination of medieval theologians, philosophers, and jurists, Andrew Latham explores how ideas about supreme political authority--sovereignty--first emerged during the high medieval period. The author provides a new model for understanding the concept of sovereignty, and traces its roots, not to the early modern or late medieval eras as do all other accounts, but to the High Middle Ages. This book aims first to provide an account of a pivotal episode in the historical evolution of the idea of sovereignty--the supreme authority to command, legislate, and judge-